Response to long-term NaHCO3-derived alkalinity in model Lotus japonicus ecotypes Gifu B-129 and Miyakojima MG-20: transcriptomic profiling and physiological characterization - Campestre, María Paula (2014)
The current knowledge regarding transcriptomic changes induced by alkalinity on plants is scarce and limited to studies where plants were subjected to the alkaline salt for periods not longer than 48 h, so there is no information available regarding the regulation of genes involved in the generation of a new homeostatic cellular condition after long-term alkaline stress. Lotus japonicus is a model legume broadly used to study many important physiological processes including biotic interactions and biotic and abiotic stresses. In the present study, we characterized phenotipically the response to alkaline stress of the most widely used L. japonicus ecotypes, Gifu B-129 and MG-20, and analyzed global transcriptome of plants subjected to 10 mM NaHCO3 during 21 days, by using the Affymetrix Lotus japonicus GeneChipH. Plant growth assessment, gas exchange parameters, chlorophyll a fluorescence transient (OJIP) analysis and metal accumulation supported the notion that MG-20 plants displayed a higher tolerance level to alkaline stress than Gifu B-129. Overall, 407 and 459 probe sets were regulated in MG-20 and Gifu B-129, respectively. The number of probe sets differentially expressed in roots was higher than that of shoots, regardless the ecotype. Gifu B-129 and MG-20 also differed in their regulation of genes that could play important roles in the generation of a new Fe/Zn homeostatic cellular condition, synthesis of plant compounds involved in stress response, protein-degradation, damage repair and root senescence, as well as in glycolysis, gluconeogenesis and TCA. In addition, there were differences between both ecotypes in the expression patterns of putative transcription factors that could determine distinct arrangements of flavonoid and isoflavonoid compounds. Our results provided a set of selected, differentially expressed genes deserving further investigation and suggested that the L. japonicus ecotypes could constitute a useful model to search for common and distinct tolerance mechanisms to long-term alkaline stress response in plants.